Silica-supported chlorometallate(iii) ionic liquids as recyclable catalysts for Diels–Alder reaction under solventless conditions. Issue 22 (21st October 2016) - Matuszek, Karolina; Chrobok, Anna; Latos, Piotr; Markiton, Magdalena; Szymańska, Katarzyna; Jarzębski, Andrzej; Swadźba-Kwaśny, Małgorzata
Abstract : The first catalytic application of supported chlorometallate(iii ) ionic liquids as recyclable heterogeneous catalysts for a Diels–Alder reaction under solventless conditions. Abstract : A range of Lewis acidic metal chlorides were tested as homogeneous catalysts in a model Diels–Alder reaction; AlCl3 and GaCl3 performed best in terms of conversion and endo  :  exo selectivity. Based on this outcome, the corresponding chlorometallate(iii ) ionic liquids were tested as homogeneous catalysts, without a decrease in performance compared to the chlorides. Finally, these ionic liquids were heterogenised by covalent tethering of the cation onto a multimodal porous silica support; such supported chlorogallate(iii ) ionic liquids are reported for the first time. Supported chlorometallate(iii ) ionic liquids were used as recyclable heterogeneous catalysts for the Diels–Alder reaction under solventless conditions. High yields (99%) and high endo -selectivities (95%) were obtained after very short reaction times (5 min) at near-ambient temperature (25 °C).